The Role of Business Acumen in Fostering Innovative Work Behavior Moderated By Innovative Climate - Stephanie Andrea Frederica Hukom; Arum Etikariena (Eduvest - Journal of Universal Studies, 2025)
This study investigates the role of business acumen (BA) in fostering innovative work behavior (IWB) among employees, moderated by an innovative climate (IC). The focus is on startups in Indonesia, where innovation is crucial for the survival and growth of companies. Using a quantitative approach, data were collected from 226 startup employees through an online questionnaire. The study employed a cross-sectional design and statistical analysis was conducted using IBM SPSS Statistics 26 and PROCESS Hayes Version 4.2. The findings reveal a significant positive relationship between BA and innovative work behavior, indicating that employees with higher BA are more likely to exhibit innovative behavior. However, the moderating effect of an innovative climate on the BA-IWB relationship was not supported, suggesting that the presence of an innovative climate does not necessarily enhance the impact of BA on innovative work behavior. The results highlight the importance of BA as a key competency for driving innovation in startups, regardless of the organizational climate. This study contributes to the literature by providing empirical evidence on the role of BA in promoting innovative work behavior and offers practical implications for startups to focus on developing BA among their employees to foster innovation. Future research should explore other potential moderators and different contexts to further understand the dynamics of BA and innovative work behavior.